Overview of diabetes, management, and pharmacotherapy updates a review - San San, Oo; Vidya, Bhagat; Zaw, Aung (2019)
Diabetes mellitus (DM) is disease of global concern. There were almost 4000 million diabetic people in 2013, and they number is expected to be up to 592 million in the next two decades. DM causes various caridovascular complications. In additiion to that, in some patients, it may lead to ocular damage, kidney diseases, nerve damage and many more complications. This review highlighs the magnitude DM, its pathopysiotholgy and complications associated with patients with DM. It also give a picture of how dietary management as well as physical activities can help in the management of body gluecose. The paper highlights the pharmacological therapy of DM using different pharmacological drug classes. In addition, it also highlights how fixed dose combination of antidiabetic medication offer a means of simplifying dosing and timing schedules for number of medications, improve efficacy, lowers risk of adverse effect and are cost effective. In conclusion this paper highlights how a collaborative effort of a diabetologists, a dietician and a pharmacologist can have an effective management of DM in patients.